Protective role of RGS2 in PM2.5-induced ovarian injury in rats: Modulation of Gq/11 signaling to maintain granulosa cell [Ca2 + ]i stability - Zhenhua Ma; Xiaohui Du; Cuizhu Zhao; Yize Sun; Yunna Jia; Xiaojun Liang; Xiuzhen Yu; Yunhang Gao (Ecotoxicology and Environmental Safety)
Fine particulate matter (PM2.5) is toxic to reproduction and can cause a range of reproductive disorders. However, the mechanisms underlying female reproductive impairment due to PM2.5 exposure are unclear. In this study, we aimed to investigate the effects of PM2.5 on rat ovaries and the underlying molecular mechanisms. Animal models showed that PM2.5 exposure induced abnormal ovarian function and disturbed ovarian-related hormone homeostasis in rats, significantly increasing the proportion of follicular atresia. This process was accompanied by ovarian inflammation, oxidative stress, apoptosis, and damage to the intracellular calcium pool (endoplasmic reticulum). Regulators of G protein signaling (RGS) are thought to play an important role in ovarian physiology. We found abnormal expressed of RGS2 in PM2.5-induced ovarian damage. Overexpression of RGS2 via adeno-associated virus type 2/9 (AAV2/9) attenuated PM2.5-induced ovarian damage in rats. In addition, rat ovarian granulosa cells were extracted. In vitro experiments showed that RGS2 overexpression attenuated the harmful effects of PM2.5 on ovarian granulosa cells. In particular, RGS2 inhibited PM2.5-induced [Ca2+]i disturbances and the signaling of two G proteins (Gnaq, Gna11), and reduced the expression levels of PLCβ and IP3R. This process effectively maintained the stability of [Ca2+]i and ATP levels in ovarian granulosa cells. These data highlight the protective role of RGS2 in PM2.5-induced ovarian damage and provide new insights into the prevention and treatment of PM2.5-induced ovarian disease.